Why migrate: For study or for work? - Elise S. Brezis (Bar-Ilan University, Department of Economics, 2016)
Over the past decades, globalization has led to a huge increase in the migration of workers, as well as students. This paper develops a simple two-step model that describes the decisions of an individual vis-à-vis education and migration, and presents a unified model, wherein the two migration decisions are combined into a single, unique model. This paper shows that under the plausible assumption that costs of migration differ over the human life cycle, the usual brain drain strategy is suboptimal. With an increase in globalization, the brain drain strategy will be replaced by the strategy of migration of students.
Keywords: F22; I23; J24; 330; Brain drain; Globalization; Higher education; Human capital; Migration; Mobility